PENGARUH LITERASI KEUANGAN SYARIAH, RELIGIUSITAS DAN PERSEPSI TERHADAP MINAT MENJADI NASABAH BANK SYARIAH PADA MAHASISWA STIE INDONESIA BANKING SCHOOL - Muhammad Rafly Tezzarino; Zulfison Zulfison (Journal of Accounting, Management and Islamic Economics, 2024)
This study aims to discuss the influences that influence the interest in becoming a customer of Islamic banks in STIE Indonesia Banking School students. The independent variables obtained from the preliminary survey results are Islamic Financial Literacy, Religiosity, and Perception. While the dependent variable obtained is the interest in becoming a customer. Analysis testinduded normality test, linearity test, and multicolinierity test. Hypothesis test using multiple regression. The population is STIE Indonesia Banking School students, with a sample of 105 respondents. The sampling technique used purposive sampling. By using a quantitative descriptive approach. The results of this study indicate that Islamic Financial Literacy has a significant positive effect on interest in becoming a customer, Religiosity has a significant positive effect on interest in becoming a customer, Perception has a significant positive effect on interest in becoming a customer.